Pengaruh Keamanan, Reputasi dan Pengalaman Terhadap Trust Pengguna Internet Untuk Bertransaksi Secara Online - Afiah, Nur (Universitas Negeri Makassar, 2018)
The aims of the research are to analyze to what extent the influence of security, reputation and experience on the trust of internet users for online interaction. The samples of the research were e-commerce users in Indonesia by taking the customers of one of the vendors of online shops, i.e. Lazada.co.id. The main instrument to collect the data was questionnaire measured by likert scale. The respondents consisted of 100 people. All questionnaires were given directly to respondents. Only 73 questionnaires were processed since 19 of them were not returned and 8 were not completed. The data were analyzed by using multiple regression analysis. The result reveal that independent variablest consisting of security, reputation, and experience have influence on customers’ trust. Security and reputation are the only variables which have a positive and significant influence on customers’ trust, while experience variable has a positive but insignificant influence. Thus, good security and reputation are very important variables in influencing the trust of e-commerce customers in Indonesia.